Connectivity‐informed adaptive regularization for generalized outcomes. Issue 1 (15th February 2021) - Brzyski, Damian; Karas, Marta; M Ances, Beau; Dzemidzic, Mario; Goñi, Joaquín; W Randolph, Timothy; Harezlak, Jaroslaw
Abstract: One of the challenging problems in neuroimaging is the principled incorporation of information from different imaging modalities. Data from each modality are frequently analyzed separately using, for instance, dimensionality reduction techniques, which result in a loss of mutual information. We propose a novel regularization method, generalized ridgified Partially Empirical Eigenvectors for Regression (griPEER), to estimate associations between the brain structure features and a scalar outcome within the generalized linear regression framework. griPEER improves the regression coefficient estimation by providing a principled approach to use external information from the structural brain connectivity. Specifically, we incorporate a penalty term, derived from the structural connectivity Laplacian matrix, in the penalized generalized linear regression. In this work, we address both theoretical and computational issues and demonstrate the robustness of our method despite incomplete information about the structural brain connectivity. In addition, we also provide a significance testing procedure for performing inference on the estimated coefficients. Finally, griPEER is evaluated both in extensive simulation studies and using clinical data to classify HIV+ and HIV− individuals. Résumé: L'un des défis en imagerie cérébrale consiste à établir les principes pour incorporer de l'information provenant de différentes modalités d'imagerie. Les données de chaque modalité sont fréquemment analysées séparément, exploitant par exemple des techniques de réduction de la dimension, ce qui conduit à une perte d'information mutuelle. Les auteurs proposent une nouvelle méthode de régularisation, griPEER (ou par vecteurs propres ridgifiés partiellement empiriques généralisés pour la régression) afin d'estimer l'association entre des caratéristiques de structures du cerveau et une variable réponse scalaire dans le cadre d'une régression linéaire généralisée. Les griPEER améliorent l'estimation des coefficients de régression en établissant les principes d'une approche permettant d'utiliser des informations externes de connectivité des structures du cerveau. À cet effet, les auteurs ajoutent au modèle de régression pénalisée généralisé un terme de pénalité dérivé de la matrice laplacienne de connectivité structurelle. Les auteurs résolvent des problèmes théoriques et calculatoires, puis démontrent la robustesse de leur méthode lorsque l'information à propos de la connectivité du cerveau est incomplète. De plus, ils présentent une procédure de test d'hypothèse permettant de l'inférence au sujet des paramètres estimés. Finalement, les auteurs évaluent les griPEER dans de vastes études de simulation et en utilisant des données cliniques afin de classifier les individus en VIH+ et VIH‐.